calisthenics as a pedagogical strategy to promote the use of free time for children aged 6 to 12 in the Granizal neighborhood of Medellín (Impetus, 2025)
This project focuses on promoting sports spaces for emerging trends in the community of Granizal, a neighborhood located in the northeastern zone, Commune 1 of Medellín. The main objective is to design a pedagogical project centered on calisthenics as an alternative for the productive use of free time among children in the neighborhood. Additionally, an inquiry was conducted into the current intervention processes in sports, physical activity, and recreation in Granizal. Methodological strategies at the local, national, and international levels were identified for working with children and youth through calisthenics. The methodology employed follows a mixed-methods approach with a descriptive scope and a non-experimental design. The target population includes community leaders and sports actors currently involved in sports and recreational initiatives in the area, as well as a group of children from a local educational institution, where an initial approach to calisthenics training was conducted. Data collection was carried out through surveys and document review. The analysis of this information allowed for a discussion on methodological aspects, highlighting key elements for strength training in children and youth. These findings serve as a foundation for developing a training plan aligned with the processes of the calisthenics discipline.
Keywords: Calisthenics; sports; free time